2020
DOI: 10.1017/dmp.2020.342
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Primary and Secondary Public Oral Health Attention: Are Dentists Ready to Face the COVID-19 Pandemic?

Abstract: Objective: Investigate knowledge and practice of Brazilian public primary and secondary healthcare dentists during COVID-19 pandemic. Methods: An online questionnaire, with socio-demographic and COVID-19 knowledge questions, was utilized. Results: A total of 4,048 dentists working in the Brazilian public primary and secondary healthcare system were investigated. 4,024 (99.41%) believe COVID-19 can be transmitted through dental procedures. It was observed a fair level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
12
0
6
Order By: Relevance
“…One of the limitations of the present study was that no distinction was made between professionals from public and private clinics. There are likely differences inherent in the practices of each sector, including operating costs and access to PPE (Vieira-Meyer et al, 2020). Another limitation concerns gender, in response to which future studies should include proportional responses from women and men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the limitations of the present study was that no distinction was made between professionals from public and private clinics. There are likely differences inherent in the practices of each sector, including operating costs and access to PPE (Vieira-Meyer et al, 2020). Another limitation concerns gender, in response to which future studies should include proportional responses from women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Also, rubber dam isolation and high power suction should be used during procedures. Thorough cleaning and disinfection of public contact areas, including door handles, chairs, and bathrooms, should also be carried out (Ahmed et al, 2020; Khader et al, 2020; Vieira-Meyer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies addressing training support or knowledge exchange between practitioner, professional regulators, and public health institutions mainly observed that communication and coordination needed improvement ( De Stafani et al 2020 ; Mustafa et al 2020 ; Sarfaraz et al 2020 ; Tysiąc-Miśta 2020 ; Vieira-Meyer et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Entretanto, na pesquisa realizada, nenhum dos voluntários que teve a doença confirmada tinha algum tipo de doença sistêmica crônica e/ou apresentou a forma grave da doença -a SARG. Os principais sinais e sintomas relatados pelos participantes são compatíveis com os apresentados na literatura 17,18,19,24 .…”
Section: Discussionunclassified
“…No que diz respeito às fontes de informação, é necessário ressaltar a importância da procedência das informações às quais os cirurgiões-dentistas se submetem 16,18 . Na literatura é possível perceber um direcionamento da maioria dos profissionais para a busca de informações nos sites de órgãos oficiais, entretanto existe também um considerável número de participantes que tem como procedência dados a partir das redes sociais 16,17,28 , as quais não se constituem em fontes consideradas confiáveis.…”
Section: Discussionunclassified